Train your brain to be a math genius - Goldsmith, Mike, frey50; Burnett, Seb. (New York, N.Y. : DK Publishing, 2012)
In this clever guide, readers previously daunted by algebra, logic, algorithms, and all things math will discover they are better at it than they thought. This resource explores the math brain and demonstrates to readers that they use math skills all the time -- they just don't know it yet. Packed with math activities and puzzles.
Math brain. Meet your brain -- Math skills --Learning math -- Brain vs. machine -- Problems with numbers -- Women and math -- Seeing the solution -- Inventing numbers. Learning to count -- Number systems -- Big zero -- Pythagoras -- Thinking outside the box -- Number patterns -- Calculation tips -- Archimedes -- Math that measures -- How big? How far? -- The size of the problem -- Magic numbers. Seeing sequences -- Pascal's triangle -- Magic squares -- Missing numbers -- Karl Gauss -- Infinity -- Numbers with meaning -- Number tricks -- Puzzling primes -- Shapes and space. Triangles -- Shaping up -- Shape shifting -- Round and round -- The third dimension -- 3-D shape puzzles -- 3-D fun -- Leonhard Euler -- Amazing mazes -- Optical illusions -- Impossible shapes -- A world of math. Interesting times -- Mapping -- Isaac Newton -- Probability -- Displaying data -- Logic puzzles and paradoxes -- Breaking codes -- Codes and ciphers -- Alan Turning -- Algebra -- Brainteasers -- Secrets of the universe -- The big quiz.
Includes index.
Keywords: Mathematical recreations; Mathematics; STEM - Education; Juvenile works